Reducing exposure of clinical research subjects to placebo treatments - Noble, Ronald E. S.; Gelfand, Lois A.; DeRubeis, Robert J. (Journal of clinical psychology, 2005)
The ethics of pill placebo and placebo psychotherapy conditions in clinical research are controversial. Even when not life threatening, mental disorders dramatically diminish the quality of life. Pill‐placebo conditions in drug treatment research have been justified on the grounds that a placebo versus standard drug comparison is necessary to test the quality of the study, viz., the assay sensitivity method. The assay sensitivity method of judging study quality, however, results in misclassification of the quality of some studies, leading to bias in effect size estimation in the context of meta‐analyses. This bias is of particular concern in relation to studies comparing psychotherapies to psychotropic drugs, which are conducted outside of the Food and Drug Administration (FDA) context. In cases in which control conditions may be justified on grounds other than as essential elements of an assay sensitivity test, statistical methods to reduce the number of study participants exposed to placebo should be strongly considered. Of the methods available, group sequential methods are the most widely used. Group sequential methods involve successive looks at accumulating data, with rules for terminating a trial (or an arm of a trial) early if results are strong enough. © 2005 Wiley Periodicals, Inc. J Clin Psychol 61: 881–892, 2005.